2017
DOI: 10.1007/s10334-016-0606-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of in vivo three-dimensional T*2 mapping using dicarboxy-PROXYL and CW-EPR-based single-point imaging

Abstract: Objectives The aim of this study was to demonstrate the feasibility of in vivo three-dimensional (3D) relaxation time normalT2∗ mapping of a dicarboxy-PROXYL radical using continuous-wave electron paramagnetic resonance (CW-EPR) imaging. Materials and methods Isotopically substituted dicarboxy-PROXYL radicals, 3,4-dicarboxy-2,2,5,5-tetra(2H3)methylpyrrolidin-(3,4-2H2)-(1-15N)-1-oxyl (2H,15N-DCP) and 3,4-dicarboxy-2,2,5,5-tetra(2H3)methylpyrrolidin-(3,4-2H2)-1-oxyl (2H-DCP), were used in the study. A clonoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…447 Relevant advances in improving the spatio-temporal resolution and sensitivity of this technique have been described and summarized recently. [448][449][450][451] A variety of aspects have to be considered when using in-vivo ESR: (i) maintenance of physiological conditions, like pH, temperature and oxygen supply during the on-going measurement, (ii) choice of a suitable spin trap, (iii) fast acquisition of data to monitor situations in real-time, (iv) improvement of signal-to-noise ratio of the data, (v) clearly defined ("simple") ESR spectra or particular aspects of the spectra, like the amplitude, and (vi) reasonable compromise between spatial resolution and signal yield. To meet all these challenges and enable reliable in-vivo ESR measurements even for very sophisticated experimental requirements, companies have developed and specifically optimized hard-and soft-ware of ESR devices.…”
Section: Applications Of Spin Traps and Spin Probes-h 2 Omentioning
confidence: 99%
“…447 Relevant advances in improving the spatio-temporal resolution and sensitivity of this technique have been described and summarized recently. [448][449][450][451] A variety of aspects have to be considered when using in-vivo ESR: (i) maintenance of physiological conditions, like pH, temperature and oxygen supply during the on-going measurement, (ii) choice of a suitable spin trap, (iii) fast acquisition of data to monitor situations in real-time, (iv) improvement of signal-to-noise ratio of the data, (v) clearly defined ("simple") ESR spectra or particular aspects of the spectra, like the amplitude, and (vi) reasonable compromise between spatial resolution and signal yield. To meet all these challenges and enable reliable in-vivo ESR measurements even for very sophisticated experimental requirements, companies have developed and specifically optimized hard-and soft-ware of ESR devices.…”
Section: Applications Of Spin Traps and Spin Probes-h 2 Omentioning
confidence: 99%
“…8 confirm that the developed tunable resonator could be used for in vivo EPR imaging of a mouse tumor-bearing leg. The 2 H, 15 N-DCP imaging probe exhibits very low toxicity [34] and none of the subject mice in our experiments died. Nevertheless, the lowest possible dose of imaging agent is always preferable for animal studies.…”
Section: In Vivo Epr Imaging Of a Mouse Tumor-bearing Legmentioning
confidence: 99%
“…EPR data-acquisition was started 5 minutes after the injection and a total of 3375 projections were acquired over the next 7.5 minutes. In our previous study, we showed that this acquisition scheme ensures a high intensity for the EPR signal and a steady concentration of 2 H, 15 N-DCP radical in the tumor tissue [34]. The incident RF power for imaging of a tumor-bearing mouse leg was 23 mW.…”
Section: F In Vivo Epr Imagingmentioning
confidence: 99%
See 2 more Smart Citations